Continuous monitoring of enzymatic activity within native electrophoresis gels: Application to mitochondrial oxidative phosphorylation complexes - Covian, Raul (2012)
Native gel electrophoresis allows the separation of very small amounts of protein complexes while retaining aspects of their activity. In-gel enzymatic assays are usually performed by using reaction-dependent deposition of chromophores or light scattering precipitates quantified at fixed time points after gel removal and fixation, limiting the ability to analyze enzyme reaction kinetics. Herein, we describe a custom reaction chamber with reaction media recirculation and filtering and an imaging system that permits the continuous monitoring of in-gel enzymatic activity even in the presence of turbidity. Images were continuously collected using time-lapse high resolution digital imaging, and processing routines were developed to obtain kinetic traces of the in-gel activities and analyze reaction time courses. This system also permitted the evaluation of enzymatic activity topology within the protein bands of the gel. This approach was used to analyze the reaction kinetics of two mitochondrial complexes in native gels. Complex IV kinetics showed a short initial linear phase where catalytic rates could be calculated, whereas Complex V activity revealed a significant lag phase followed by two linear phases. The utility of monitoring the entire kinetic behavior of these reactions in native gels, as well as the general application of this approach, is discussed.